2020
DOI: 10.32598/bcn.11.covid19.651.4
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Anxiety, and Depression Levels Among Healthcare Staff During the COVID-19 Epidemic

Abstract: In the Coronavirus Disease 2019 (COVID-19) pandemic, medical staff Are in direct contact with the patients and experience high work pressure. Direct contact with the patients could create some psychological problems in this group. Thus, the prevalence of such problems must be investigated in them. The present study aimed to determine the level of stress, anxiety, and depression among the healthcare staff in Zanjan City, Iran, during the COVID-19 epidemic. Methods: This descriptive study has a cross-sectional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
4
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 14 publications
(23 reference statements)
4
37
4
3
Order By: Relevance
“…The pattern of findings suggested that health anxiety was the complex result of personal concerns [ 5 ], contact with close acquaintances infected with COVID-19 [ 5 ], and working on the frontline [ 13 , 17 ], while age, educational background, and gender were unrelated. Such lack of effects have been reported previously [ 14 ], though for age [ 5 , 15 ], educational background [ 5 , 15 ], and gender [ 15 , 16 ], opposite findings have also been reported.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The pattern of findings suggested that health anxiety was the complex result of personal concerns [ 5 ], contact with close acquaintances infected with COVID-19 [ 5 ], and working on the frontline [ 13 , 17 ], while age, educational background, and gender were unrelated. Such lack of effects have been reported previously [ 14 ], though for age [ 5 , 15 ], educational background [ 5 , 15 ], and gender [ 15 , 16 ], opposite findings have also been reported.…”
Section: Discussionmentioning
confidence: 45%
“…As regards the psychological health of Iranian hospital staff members, higher scores for job-related stress and burnout were related to working on the frontline [ 13 ], irrespective of age, job experience, or the social support of friend and families [ 14 ]. In contrast, among frontline nurses with an average age of 40.6, higher age, higher educational degrees, and being male predicted lower stress [ 15 , 16 ]. A higher task load was associated with lower general health [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study during the H1N1 outbreak, hospital staff who were in their 20's had greater anxiety about becoming infected than did older staff ( 103 ). During COVID-19, HCW who were younger were more likely to experience higher levels of post-traumatic stress symptoms, depression, anxiety, and acute stress compared to older HCW ( 23 , 26 28 , 30 , 32 , 42 , 49 , 54 , 55 , 57 , 61 , 65 , 71 , 75 , 78 , 89 , 90 , 117 , 118 , 121 , 123 , 127 , 131 , 149 , 153 , 154 ). In contrast, eight studies conducted during COVID found that HCW who were older were at greater risk of experiencing higher levels of psychological distress ( 40 , 66 , 86 , 95 , 102 , 114 , 122 , 132 ).…”
Section: Resultsmentioning
confidence: 99%
“…No obstante, observamos asociaciones particulares entre algunas variables, concretamente en el período 2 las personas que habían terminado la secundaria o la universidad percibieron mayor estrés. Nuestros resultados no se encuentran en línea con lo observado en el modelo general y lo hallado en estudios previos (e.g., Hosseinzadeh-Shanjani et al, 2020;Matus et al, 2020;Odriozola-González et al, 2020), aunque están en concordancia con lo observado por otras investigaciones (e.g., Marquina Lujan, 2020; Song et al, 2020). Una posible explicación a este resultado podría deberse a lo expresado por .…”
Section: Discussionunclassified
“…Otras investigaciones reportaron que el nivel de estrés percibido durante la pandemia varía según el nivel educativo de las personas. Ahora bien, los resultados encontrados son contradictorios ya que en algunas investigaciones se observó que un menor nivel de instrucción se asocia a mayores niveles de estrés (e.g., Hosseinzadeh-Shanjani et al, 2020;Matus et al, 2020;Odriozola-González et al, 2020) en tanto que en otras se halló lo opuesto (p.e., Marquina Lujan, 2020; Song et al 2020).…”
unclassified